Islamic Perspective in E-Service Quality-based Knowledge Sharing on Islamic Hospital Employee Performance Improvement - Roosallyn Assyofa, Allya; Malik A. Rohandi, Moch.; Mustika Rani, Asni; Maudina, Triputri (KnE Social Sciences, 2023)
Technological developments now greatly affect the activities of health organizations and are expected to encourage better hospital performance. One of the efforts that can be made to increase employee knowledge related to technological developments is through knowledge sharing. Measuring the quality of hospital management information systems from the user’s point of view using the e-service quality method. The study aims to determine the effect of knowledge sharing and e-service quality information systems on employee performance in Islamic hospitals that have followed global budget rules in West Java. This research uses a quantitative method with a causal research type. Information is collected directly from the field to find out the opinion of the respondents on the object being studied. The researchers used judgment sampling with the number of samples obtained using the Bernoulli method with an error of 5% so that the minimum number of respondents was 128. The research data were obtained through the results of interviews and questionnaires. The data were processed, analyzed, and then conclusions were drawn using the cross-sectional method. The results of the analysis show that both knowledge sharing and e-service quality are in good category and employee performance is in the very good category. The variables of knowledge sharing and e-service quality both partially and simultaneously have a positive and significant effect on employee performance with a moderate effect. Keywords: e-service quality, employee performance, Islamic hospital, knowledge sharing